Influence of biological sex, age and smoking on Graves’ orbitopathy – a ten-year tertiary referral center analysis - Oeverhaus, Michael; Winkler, Luisa; Stähr, Kerstin; Daser, Anke; Bechrakis, Nikolaos; Stöhr, Mareile; Chen, Ying; Eckstein, Anja (Frontiers in Endocrinology, 2023)
Purpose Severity of Graves’ orbitopathy (GO) shows wide individual differences. For optimal treatment, it is important to be able to predict the natural course of the disease as accurate as possible to counteract with anti-inflammatory and surgical treatment. Therefore, we aimed to further elucidate the impact of sex, age and smoking on GO. Methods We collected the clinical and demographic data of all patients of our tertiary referral center from January 2008 till December 2018 and analyzed it with descriptive statistics. Only patients with a complete data set were included in the further analysis. Odds ratio’s for moderate-to-severe and sight-threatening GO in relation to age, sex and smoking were calculated by means of multivariate logistic regression models. Results We evaluated the data of 4260 patient with GO and complete data sets. Most of these were women (83%). There were no significant differences between male and female patients regarding smoking habits and thyroid treatment. Men were significantly older at initial manifestation of TED (51.8 vs. 49.9y, p<0.01) and showed significant more often severe stages (61% vs. 53%, p<0.0001). Therefore, they needed significantly more intense treatment with steroids, irradiation, orbital decompression and muscle surgery. In multivariate logistic regression analyses age (OR 0.97, 95% CI:0.97-0.98, p<0.0001), male sex (OR 1.64, 95% CI:1.38-1.9, p<0.0001), smoking (OR 1.19, 95% CI:1.04-1.36, p=0.01), Grave’s disease (OR 1.55, 95% CI:1.26-1.90, p<0.0001) and history of radioiodine treatment (RAI) (OR 2.44, 95% CI:2.10-2.86, p<0.0001) showed an significant association with severe stages of GO. Discussion Our retrospective analysis showed once more that women are more often afflicted by GO. In contrast, men seem to be more severely afflicted and in need of anti-inflammatory and surgical treatments. This might be due to a different approach to the health system and resilience to GO specific symptoms, as well as previously described worse thyroid control. Estrogen mediated effects might also play a role as in other autoimmune diseases and should be subject of further trials. Besides the biological sex, smoking could again be confirmed as serious risk factor for severe GO. Of note, RAI was associated with more severe stages of GO, which should be subject to further investigation.